Evidence for Non‐Mendelian Inheritance in Spastic Paraplegia 7. Issue 7 (17th February 2021) - Estiar, Mehrdad A.; Yu, Eric; Haj Salem, Ikhlass; Ross, Jay P.; Mufti, Kheireddin; Akçimen, Fulya; Leveille, Etienne; Spiegelman, Dan; Ruskey, Jennifer A.; Asayesh, Farnaz; Dagher, Alain; Yoon, Grace; et al.
Abstract: Background: Although the typical inheritance of spastic paraplegia 7 is recessive, several reports have suggested that SPG7 variants may also cause autosomal dominant hereditary spastic paraplegia (HSP). Objectives: We aimed to conduct an exome‐wide genetic analysis on a large Canadian cohort of HSP patients and controls to examine the association of SPG7 and HSP. Methods: We analyzed 585 HSP patients from 372 families and 1175 controls, including 580 unrelated individuals. Whole‐exome sequencing was performed on 400 HSP patients (291 index cases) and all 1175 controls. Results: The frequency of heterozygous pathogenic/likely pathogenic SPG7 variants (4.8%) among unrelated HSP patients was higher than among unrelated controls (1.7%; OR 2.88, 95% CI 1.24–6.66, P  = 0.009). The heterozygous SPG7 p.(Ala510Val) variant was found in 3.7% of index patients versus 0.85% in unrelated controls (OR 4.42, 95% CI 1.49–13.07, P  = 0.005). Similar results were obtained after including only genetically‐undiagnosed patients. We identified four heterozygous SPG7 variant carriers with an additional pathogenic variant in known HSP genes, compared to zero in controls (OR 19.58, 95% CI 1.05–365.13, P  = 0.0031), indicating potential digenic inheritance. We further identified four families with heterozygous variants in SPG7 and SPG7 ‐interacting genes ( CACNA1A, AFG3L2, and MORC2 ). Of these, there is especially compelling evidence for epistasis between SPG7 and AFG3L2 . The p.(Ile705Thr) variant in AFG3L2 is located at the interface between hexamer subunits, in a hotspot of mutations associated with spinocerebellar ataxia type 28 that affect its proteolytic function. Conclusions: Our results provide evidence for complex inheritance in SPG7 ‐associated HSP, which may include recessive and possibly dominant and digenic/epistasis forms of inheritance. © 2021 International Parkinson and Movement Disorder Society